Simulazioni geospaziali I sistemi pedestri - Bartoli, Francesco (GEOmedia, 2008)
Geospatial solutions: the pedestrian systems Investigating alongside Decision Support System simulation based models are centric. Even though Geographic Information Systems do not get in touch with Agent Based Models sooner, geospatial simulations provide several enhancements in emergency evacuation scenarios. In a small scale pedestrian movement modelling which depicts crowd behaviour and gathering as well as ingress and egress situations from large venue where panic usually rises. Crowd managers can be supported in their decisions by running the same model against different conditions such as spatial constraints to take a turn for the better and avoid congestions as well crushing and trampling phenomena.